AKTIVITAS ANTITUMOR DAN PREBIOTIK SENYAWA TURUNAN EPIGLUKAN: (13),(16)--GLUKAN EKSTRASELLULER DARI Epicoccum nigrum EHRENB. EX SCHLECHT - Jay Jayus; Nuriman Nuriman; Sony Suwasono (JURNAL AGROTEKNOLOGI, 2011)
Extracellular epiglucan produced by Epicoccum nigrum has been examined by in vitro analysis to show its potency as an antitumor substance against leucemia cell. The aims of this study were to ditermine the LC50 value and prebiotic activities of native and derivated epiglucan. The epiglucan was modified by sulfation and carboxymethilation methods. The result showed that LC50 of native epiglucan occur at concentration of 22 g/ml. This substance was chemically modified through sulfation and charboxymethilation process in order to increase its antitumor activity. Based on the value of LC50, the sulfated and carboxymethylated epiglucan have higher activity against leucemia cell compare to that of unmodified epiglucan. The LC50 value of suphated epiglucan is 14 µg/L, while the carboxymethylated one is 13 µg/L. Prebiotic activities of both sulfated and carboxymethylated epiglucan were also higher compare to the unmodified glucan since these two derivatives are able to elevate the growth rate of probiotic microorganism such as Lactobacillus casei, L. acidophilus and L. rhamnosus. Keywords: antitumor, extracellular epiglucan, Epicoccum nigrum, charboxymethilation, sulfation